The level of critical thinking in mathematics among students of the College of Basic Education (Journal of the College of Basic Education, 2022)
The study aimed to identify the level of critical thinking in mathematics among students of the College of Basic Education.The study identified critical thinking skills (deduction, deduction, knowing assumptions, evaluating arguments, and interpretation).The study sample consisted of (108) male and female students who represented all students of the fourth stage  Department of Mathematics  Morning study in the College of Basic Education for the academic year 2008-2009.The study tool consisted of a test - prepared by the researcher - similar to the (Watson-Gleaser) scale for critical thinking consisting of (75) items, and each sub-test for its domains consisted of (15) items, and its psychometric characteristics were confirmed.The study concluded that the level of critical thinking in mathematics among students was acceptable compared to the acceptable performance level of 70%, as determined by a group of experts.